Association of Daytime Somnolence With Executive Functioning in the First 6 Months After Adolescent Traumatic Brain Injury. Issue 7 (29th January 2013) - Osorio, Marisa B.; Kurowski, Brad G.; Beebe, Dean; Taylor, H. Gerry; Brown, Tanya M.; Kirkwood, Michael W.; Wade, Shari L.
Abstract : Objective: To determine the relationship between severity of injury and self‐reports and parent reports of daytime somnolence in adolescents after traumatic brain injury (TBI), and to determine the relationship between daytime somnolence and self‐report and parent report of executive functioning in daily life. Design: Cross‐sectional study conducted within the first 6 months (mean ± standard deviation 14.97 ± 7.51 weeks) after injury. Partial correlation controlling for injury severity was used to examine the associations of TBI severity with daytime somnolence and the association of daytime somnolence with executive functioning. Setting: Outpatient visits at 3 children's hospitals and 2 general hospitals with pediatric trauma commitment. Participants: A total of 102 adolescents, 12‐18 years old, who sustained moderate‐to‐severe TBI (n = 60) or complicated mild TBI (n = 42). Main Outcome Measurements: Parent‐report Sleepiness Scale, Epworth Sleepiness Scale (youth report), Behavior Rating Inventory of Executive Function (BRIEF) (self‐report and maternal report). Results: Adolescents who sustained moderate‐to‐severe TBI had increased daytime somnolence compared with those with complicated mild injuries in the parent report but not in the youth report. Based on the parent report, 51% of adolescents with moderate‐to‐severe TBI showed significant daytime somnolence compared with 22% of those with complicated mild TBI. The parent report of daytime somnolence was associated with executive dysfunction on both the BRIEF self‐report and parent report; however, the youth report of daytime somnolence was associated only with the BRIEF self‐report. Conclusions: The parent report of daytime somnolence correlated with TBI severity and predicted executive functioning difficulties of the teens in everyday circumstances. Although a correlation between daytime somnolence and executive dysfunction were also apparent on self‐report, this did not differ based on injury severity. Teens tended to report fewer difficulties with executive function, which suggests that the teens have decreased awareness of their impairments.